(untitled) (Research, Society and Development, 2021)
Include the abstract in English. (TNR font 10 – simple space) The objectives of the study were to evaluate the fertility of the Yellow Latosol medium texture in plants of cupuassu (Theobroma grandiflorum) progeny 61 and to characterize the visual symptoms of macronutrient and micronutrient deficiencies. The plants were grown in nutrient solution containing all macronutrients and micronutrients and in solutions with omission of N, P, K, Ca, Mg, S, B, and Zn, using the missing element technique. The experimental design was completely randomized with eleven treatments and five replications. Growth was evaluated through production and dry matter at 60 days after planting. The progeny showed market potential, as it is more productive than the others, but it presents nutritional requirements similar to those of the cultivars already studied. The nutrient required in greater quantities by the culture was nitrogen, but the omission, but limiting, was that of potassium for biometric variables. The best treatment was complete followed by omission of zinc, but the difference between them was significant. The levels of nutrients in the leaves were similar to those found by other authors in other cultivars. The decreasing order of treatments was C> Zn> T> N> P> Ca> Mg> S> B> K.